Examining the Influence of ICT Penetration on Gender Disparities: A Data Panel Econometric Analysis of the Seven Southeast Asian Developing Countries - Wijaya, Chandra Henryawan; Basyir, Naail Daffa; Hasudungan, Albert; Desfiandi, Alvin (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
The aim of the study is to analyze to which Information and Communications Technology (ICT) penetration affects gender disparities in seven Southeast Asia’s developing countries. ICT indicators are measured through the individuals using the internet, mobile phone subscriptions, and internet subscriptions. Aside, the seven Southeast Asia’s developing countries include Indonesia, Cambodia, Laos, Malaysia, Thailand, Philippines, and Vietnam. These countries are selected as they have comparable economic development stage from lower to upper-middle income economics on the basis 2022’s World Bank Country Income Classification. The data panel econometrics is carried out to measure the effect of the independent variables towards gender disparity. Gender disparity is represented by the Gender Inequality Index. The time series data is yearly from 2000 to 2022. The econometric assessment shows the individual internet ownership and subscription have a negative and significant effect to gender disparity. It means that more internet penetration can lower the gender disparity in those seven countries. The academic implication is to enhance economic consideration towards more internet penetration and access to reduce gender disparity. In the heart of policymaking, our research indicates more internet accessibility to reduce gender disparity. As in the common knowledge, the internet is a source of information and knowledge to society